Ethnopsychological Consultation: a Tool for Strengthening of Partnerships in Multicultural Social Work - Galesi, Davide (Participatory Social Work: Research, Practice, Education, 2019)
During international migration immigrants and refugees are exposed to difficulties that can lead to various psychosocial problems. In order to guarantee appropriate support, social workers are required to investigate and comprehend these clients’ psychological and socioanthropological background, especially when they are not socialized into Western culture. In multicultural social work, the international debate on how best to reach this objective has developed several theoretical perspectives. Against such a backdrop, this chapter investigates ethnopsychological consultation as a professional tool that can be used by social workers, educators and health care professionals. A case study using participant observation in Italy serves as the basis for the discussion on how this technique puts the theoretical principles of multicultural social work into practice, highlighting how it helps professionals establish stronger partnerships with their clients.